Elastic stable intramedullary fixation using epibloc versus crossed kirschner wires fixation for distal forearm fractures in children: A retrospective analysis - Rocco De Vitis; Marco D'Orio; Marco Passiatore; Andrea Perna; Vitale Cilli; Giuseppe Taccardo (Wolters Kluwer Medknow Publications, 2022)
Background: Childrens' distal forearm fractures (DFFs) could be treated conservatively with closed reduction and immobilisation, but post-reduction displacements often occur. Displaced DFF should be surgically fixed, to avoid further displacement. Nevertheless, immobilisation after surgery is recommended. Epibloc system (ES), a system of stable elastic nail fixation, is widely used to stabilise adults extra-articular distal radius fractures, with advantages to not requiring post-surgical immobilisation. The present investigation represents a retrospective analysis of paediatric patients with DFF treated with ES applied with a minimal technical variation, to fix both ulna and radius fractures using a unique device. Materials and Methods: A retrospective analysis was performed on 44 children (age 6-11 years) who underwent closed reduction and internal fixation because of DFF (both ulna and radius). Group A (21 patients): ES fixation. Group B (23 patients): K-wires and short arm cast fixation. The primary outcome was the subsistence of reduction monitored through X-rays. The secondary outcome was the measurement of active range of motion (AROM) and the time of recovery. Results: No differences were observed comparing Group A and B in terms of the maintenance of reduction (P > 0.05). Seven days after the implant removal, patients in Group A reached significantly better results compared to patients in Group B in terms of AROM (P < 0.05). No differences were revealed in terms of complications between the two groups. Conclusion: ES applied with a minimal technical variation is safe and effective in treating distal ulna and radius fractures, with minimal requirement of post-surgical rehabilitation.